Educating Children in Poor Countries - Jenkner, Eva.; Hillman, Arye. (Washington, D.C. : International Monetary Fund, 2004)
In an ideal world, primary education would be universal and publicly financed, and all children would be able to attend school regardless of their parents' ability or willingness to pay. In many poor countries, however, governments lack either the financial resources or the political will to provide each child with a basic education, despite the benefits that would accrue not only to individuals but to society as a whole. In some of these countries, parents cover part or all of the cost of their children's education. This paper explores the pros and cons of user payments.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: EI; School Attendance; School Enrollment; School; User Payment; Chad